IMPLEMENTATION OF DIGITAL SPEAKER TRAINING IN BUILDING ENTREPRENEURIAL CONTENT FOR BUDDHA SAMANERA AND ATTHASILANI PADEPOKAN DHAMMADIPA ARAMA BATU - Herman (Nusantara Economics and Entrepreneurships Journals, 2023)
The phenomenon of the development of social media in delivering sermons makes an opportunity for novices and atthasilani to innovate to be able to compete. But it is a challenge because of the need to increase skills in carrying out all processes of technological development. Preaching with the use of technology has been widely applied to other beliefs in order to entice people to listen to sermons. Padepokan Dhammadipa Arama Batu seeks to present graduates who can compete and increase the interest of the devotees to follow every Buddhist teaching. This study uses a qualitative phenomenological approach in which researchers raise the phenomenon that occurs, namely the development of digital speakers in building an entrepreneurial spirit amid competition and the times. Collect data in the field and study it in a triagulation technique to combine data collection and sources. The implementation of digital speaker training provides an increase in skills possessed, forms new insights, pioneers preach in a more modern style and method with the aim of being able to increase the interest of the faithful in listening to the Dhamma being conveyed. In addition to instilling an entrepreneurial spirit in accordance with the teachings of the Buddha which prioritizes the benefits of others without harming other creatures. The selection of entrepreneurial material for samanera and atthasilani cannot be separated from the phenomenon that occurs, namely humans cannot be separated from the process of seeking sustenance to continue life. So that the need for guidance and information to guide people to stick to the search for material in the world according to Buddhist teachings. Packing sermons in digital speakers gives a new perspective and style. However, this development must be followed by the procurement and improvement of supporting facilities to assist competent and competitive human resources so that the regeneration of samanera and atthasilani can be established and developed